THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP AND QUALITY OF WORK LIFE ON SOLDIER PERFORMANCE WITH ORGANIZATIONAL COMMITMENT AS A MEDIATING VARIABLE(STUDY AT MILITARY RESORT COMMAND/ KOREM 101/ ANTASARI) - Rini Rahmawati; Ari Aryanto; Muhammad Ary Aprian Noor (INJOSEDU: International Journal of Social and Education, 2025)
The purpose of this research is to investigate the effect of transformational leadership and quality of work life on soldier performance with organizational commitment as a mediating variable at Military Resort Command/Korem 101/Antasari. The research method is quantitative using partial least square structural equation modelling analysis with data analysis using Smart PLS 3.0 software. The study involved 151 respondents is a soldier at Korem 101/Antasari. The type of variable scale used is the ordinal scale. The rating scale for each statement uses a rating scale technique with a likert scale type. Online questionnaires are distributed, the data analysis stage is the outer model test, namely the validity and reliability test and the inner model test, namely the hypothesis test or significance test. The independent variable of this research is transformational leadership and quality of work life. The dependent variable is soldier performance. Organizational commitment as a mediating variable. Online questionnaires based on the results of research data analysis it was found that there wasa significant relationship between Quality of Work Life and Organizational Commitment. There is a significant relationship between Quality of Work Life and Soldier Performance. There is a significant relationship between Organizational Commitment and Soldier Performance. Organizational commitment is able to mediate between Quality of Work Life, and Soldier Performance. There is no significant relationship between Transformational Leadership and Organizational Commitment. There is no significant relationship between Transformational Leadership and Soldier Performance. Organizational commitment is unable to mediate the influence between transformational leadership and soldier performance